Tusk or Bone? An Example of Ivory Substitute in the Wildlife Trade - Margaret E. Sims; Barry W. Baker; Robert M. Hoesch (Ethnobiology Letters, 2011)
Bone carvings (and other ivory substitutes) are common in the modern-day lucrative international ivory trade.  Souvenirs for unknowing travelers and market shoppers can be made of non-biological material (plastic "ivory" beads) or skillfully crafted natural objects made to resemble something other than their true origin.  Many of these items are received at the U. S. National Fish and Wildlife Forensics Laboratory (NFWFL) for species identification as part of law enforcement investigations.  Morphologists at the Lab often receive uniquely carved ivory items that have been imported with little or no documentation.  In recent years, analysts examined several purported ivory tusks suspected to be walrus, a protected marine mammal.  After examination, the Lab determined their origin as carved leg bones of cattle using principles and methods of zooarchaeology and ancient DNA analysis.  The naturally long and straight ungulate metapodials had been cut, carved, filled, stained, and polished to closely resemble unmodified ivory tusks.  Morphological species identification of these bones proved to be a challenge since diagnostic characters of the bones had been altered and country of origin was unknown. Genetic analysis showed that the bones originated from cattle.  While bone is commonly used as a substitute for ivory, this style of artifact was not previously documented in the wildlife trade prior to our analysis.  Archaeological ethnobiologists commonly encounter bone tools and other forms of material culture from prehistoric and historic contexts; in this case bone tools come from a modern context, thus the application of methods common in zooarchaeology are situated in wildlife forensics.  In addition, results reported here pertain to cross-cultural ivory trade and conservation science.